2020
DOI: 10.1186/s40734-020-00089-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact and challenges associated with Parkinson’s disease patient care amidst the COVID-19 global pandemic

Abstract: Background: COVID-19 has made itself known to health care providers and families across the world in a matter of months. While primarily a respiratory disorder, it has also been shown to cause neurological symptoms, which can be a concern for Parkinson's disease (PD) patients. Although PD is not as common as other conditions such as cardiovascular diseases, it affects millions of patients around the world whose care has been affected by the global pandemic. Objectives: The aim of this review is to provide insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 32 publications
0
37
0
2
Order By: Relevance
“…Some elective surgical procedures like deep brain stimulation (DBS) have been delayed, leaving some PD patients facing barriers in achieving optimal care until further notice. 20 Only one participant in this study was waiting for his DBS appointment, which has been cancelled for the time being, while many other participants expressed a short-term understanding of the delay in clinical care but foresee progressive PD problems if the clinical visitations do not resume soon.…”
Section: Clinical Carementioning
confidence: 98%
“…Some elective surgical procedures like deep brain stimulation (DBS) have been delayed, leaving some PD patients facing barriers in achieving optimal care until further notice. 20 Only one participant in this study was waiting for his DBS appointment, which has been cancelled for the time being, while many other participants expressed a short-term understanding of the delay in clinical care but foresee progressive PD problems if the clinical visitations do not resume soon.…”
Section: Clinical Carementioning
confidence: 98%
“…Although data are thus far limited, it is conceivable that PD patients may be at elevated risk of severe respiratory complications following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or even unfavourable outcomes. In addition, it has been suggested that other indirect factors of the pandemic, including increased stress, self-isolation, and anxiety, as well as prolonged immobility, may further exacerbate the outcome of PD patients affected by COVID-19 [ 20 , 21 ]. Currently, there is insufficient evidence to show that a pre-existing diagnosis of PD increases the risk of COVID-19 or mortality, and contradictory results have been reported from small samples of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Os sintomas motores da DP podem ser acentuados por agravo de qualquer doença acometida pelo paciente, como por exemplo, as virais respiratórias no caso da COVID-19. Os pacientes quando acometidos por uma doença viral, podem notar agravo nos sintomas de bradicinesia, de rigidez ou ter e/ou piorar quadros de alucinações, podendo ou não estes estarem associados à sintomatologia do quadro clínico da infecção pelo vírus (Elbeddini et al, 2020).…”
Section: Introductionunclassified
“…Embora todos sejam suscetíveis à infecção, pacientes idosos apresentam mais chances de sintomas graves e morte. O perfil do paciente com DP comporta idosos comumente portadores de outras comorbidades como doenças cardiovasculares, doenças mentais, o que agrava a classificação nos grupos de alto risco relacionados à COVID-19 (Elbeddini et al, 2020).…”
Section: Introductionunclassified